(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article analyzes the creative methods used to effectively explain the topic of "development" in the process of primary education, that is, approaches through game technologies, visual tools, interactive exercises, problem questions. The importance of non-traditional approaches in teaching the levels, formation and types of structures of ravishes will be shown.